APPLICATION OF STRING MATCHING USING BOYER MOORE ALGORITHM IN THE APPLICATION OF DICTIONARY LIVESTOCK TERMS - Wahyu Suci Saputri; Riska Dhenabayu; Filda Febrinita (JOSAR (Journal of Students Academic Research), 2018)
Difficulty in getting a dictionary of the term livestock is an obstacle for the academic community of the Faculty of Animal Husbandry, Balitar Islamic University to find out the meaning of the term livestock. Along with the progress of the times, the need for a dictionary can certainly be met with technological sophistication, one of which is through a dictionary application. This study designed the term dictionary dictionary application by applying the Boyer Moore algorithm matching string. This translation process is carried out in the form of words where each keyword term searched will appear along with the meaning of the term farm. The term farm dictionary application is designed using Microsoft Visual Visio 2007 and the application is implemented based on the website. The boyer moore string matching algorithm does word matching by applying the FilterString function and the search function. The FilterString function detects each character in a keyword while the search function matches keywords from the FilterString function with terms in term data in the database. The results of beta testing showed that the system obtained an average value of 71.58%, meaning that users had high satisfaction with the term dictionary application.